Implications for general practitioner of evolution of incidence rates of COVID-19 breakthrough infections in vaccinated people as of December 2021 with the highest spike of infections of the entire pandemic - Jose Luis Turabian (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
From the extension of the COVID-19 vaccination in December 2020 to the end of the summer of 2021, cases of breakthrough Infection in vaccinated people were rare and their attack rate was low (0.01%-5.5%). Of course, in light of the increase in vaccination rates, breakthrough Infection in vaccinated people progressively could represent the majority of all COVID-19 cases. But at the end of December 2021, the world registered the highest number of COVID-19 infections in a week. Just a few months ago, the evolution that seemed reasonable was thought to be the elimination of the pandemic. But Delta, and Omicron after, arrived; and we weren't expecting them. The latter clearly evades immunity against vaccine-based infection, and breakthrough infections are becoming more common. This situation causes certain effects at the community level and has implications for the general practitioner: 1. Availability of vaccines has brought about a change that, when they began to be applied, seemed much more promising than it is currently; 2. This context may increase denial regarding COVID-19 vaccines; 3. Vaccination has contributed to an appreciable reduction in the number of serious and critical clinical cases; 4. Attack rates in vaccinated will increase as the proportion of vaccinated increases; 5. The importance of booster doses when immunity falls; 6. Incidence rates at the community level and official diagnostic tests will no longer be important.